Critical analysis of factors determining mechanical failures in proximal femoral nailing - Ramachandran, Karthik; Arvind Manoj, K. K.; Sankar, A. Vishnu (International Journal of Research in Orthopaedics, 2019)
Background: Intertrochanteric fractures are one of the commonest fractures encountered in elderly population. Though there are various implants, proximal femoral nail has been the standard choice for management of unstable fractures. Inspite of its biomechanical advantages, various complications like screw cut out, Z effect, reverse Z effect does occur in proximal femoral nailing. The aim of the study is to analyse various factors determining the mechanical failures in patients operated with proximal femoral nail. Methods: This is a prospective study conducted in our institution from June 2014 to May 2018. The study included 72 patients with unstable intertrochanteric fractures treated with proximal femoral nail. All patients were followed for average period of 2 years. Functional outcome was assessed using Harris Hip score. Results: Among the patients 33% had excellent outcome. 42% had good and 14% had fair outcome. 11% of cases ended with poor outcome. Mechanical failure rate was less in patients with positive medial cortical support (PMCS) and in patients with tip apex distance difference between antirotation screw and lag screw (TADAR -TADLS) more than 15 mm. Whereas the difference in the position of lag screw centre had no significant influence in the mechanical failure rate in our study. Conclusions: From our study we like to conclude that the fracture reduction with positive medial cortical support and the TAD difference play a major role in determining the incidence of mechanical failure in proximal femoral nailing.